(untitled) (Bangladesh Journal of Medicine, 2024)
Nontuberculous mycobacterial (NTM) o Atypical mycobacterial (ATM) infection is becoming an upcoming challenge for the clinicians. Atypical Mycobacterial infections range from pulmonary to extra pulmonary including skin and soft-tissue infections, traumatic and surgical wound infections, catheter and implant-associated infections. They are commonly misdiagnosed as tuberculosis caused by M. tuberculosis (MTB). Appropriate diagnostic methods and tools are essential in order to facilitate the differential diagnosis of Atypical Mycobacterium from MTB infections. We aimed to collect data available on Atypical Mycobacterium for diagnosis and appropriate treatment and to create awareness among the physician to combat with challenges. Bangladesh J Medicine 2025; 36: 15-18